The Impact of Chemotherapy on Arterial Stiffness and Ventricular-Arterial Coupling in Women with Breast Cancer - Nikolaos P. E. Kadoglou; Alexandriani Dimopoulou; Irene Tsappa; Pampina Pilavaki; Anastasia Constantinidou (MDPI AG, 2024)
Background: The cardiac toxicity of chemotherapy for breast cancer is not uncommon and has been associated with elevated morbidity and mortality. In the present study, we assessed the impact of chemotherapy on cardiovascular function by assessing the cardio-ankle vascular index (CAVI), global longitudinal strain (GLS) and ventricular-arterial coupling (VAC: CAVI/GLS ratio) in chemotherapy-treated women. Methods: This prospective study enrolled 78 women with breast cancer who were receiving anthracycline-based chemotherapy +/− anti-HER2 therapy (trastuzumab +/− pertuzumab). Forty-one age-matched healthy women served as controls. We comparatively evaluated left ventricular ejection fraction (LVEF), CAVI, GLS and VAC, between the chemotherapy and control groups. We also assessed their changes over time (baseline, 3-month and 6-month time point) and their independent association with the incidence of cancer therapy-related cardiovascular dysfunction (CTRCD) in the chemotherapy group. Results: In comparison to healthy controls, women receiving chemotherapy presented with significantly higher GLS (from −21.02 ± 2.09% to −19.01 ± 2.81%, p < 0.001) and VAC (−0.36 ± 0.06 to −0.41 ± 0.11, p < 0.001). The presence of CTRCD was associated with a further increase in GLS and CAVI and a significant decline in LVEF and VAC compared to CTRCD-free women (p < 0.001). Baseline, CAVI, GLS and VAC were independently associated with CTRCD development during follow-up. Conclusion: Women with breast cancer undergoing chemotherapy displayed abnormal levels of CAVI, VAC and GLS, compared to healthy individuals. Those effects on VAC and CAVI were more exaggerated among women with CTRCD, implicating their potential use to refine screening and therapeutic strategies for this specific population.